Illuminating the Role of Vpr in HIV Infection of Myeloid Cells - Nodder, Sarah Beth; Gummuluru, Suryaram (Frontiers in Immunology, 2019)
Vpr is a 14 kDa accessory protein conserved amongst extant primate lentiviruses that is required for virus replication in vivo. Although many functions have been attributed to Vpr, its primary role, and the function under selective pressure in vivo, remains elusive. The minimal importance of Vpr in infection of activated CD4+ T cells in vitro suggests that its major importance lies in overcoming restriction to virus replication in non-cycling myeloid cell populations, such as macrophages and dendritic cells. HIV-1 replication is attenuated in the absence of Vpr in myeloid cells such as monocyte-derived dendritic cells (MDDCs) and macrophages, and is correlated with the ability of Vpr to overcome a post-integration transcriptional defect in these cells. Intriguingly, recent identification of the human hub silencing (HUSH) complex as a target for DCAFCRL4-mediated degradation by numerous ancestral SIV Vpr alleles, and the Vpr paralog Vpx, signifies the potential function of HIV-1 Vpr to alter yet-to-be identified chromatin remodeling complexes and prevent host-mediated transcriptional repression of both invading viral genomes and pro-inflammatory responses. Since myeloid cells constitute an important bridge between innate and adaptive immune responses to invading pathogens, here, we seek to illustrate the numerous means by which Vpr manipulates their cellular environment and facilitates virus replication, thus promoting myeloid cell-dependent HIV replication, transmission and systemic dissemination.